Perancangan Aplikasi Edukasi Kesehatan Berbasis Multimedia - Elisabeth (TEMATIKA: Jurnal Penelitian Teknik Informatika dan Sistem Informasi, 2014)
Healthy is the right of every person. Therefore, every person has the same rights in obtaining access to the resources in the health field. However, there are limitations in the access and a minimal level of public knowledge about health wellness does not end up making every person the same. It is seen from the high number of deaths in children under five due to diarrheal diseases. To that end, Indonesia Sehat Programme 2025 in which people's behavior is proactive to maintain and improve health and prevent the risk of developing the disease then designed a wellness educational applications using multimedia expansion method and use the library as a method of research studies. The results of this study indicate that the application to help people obtain educational information about the disease, especially diarrhea.